2016
DOI: 10.2117/psysoc.2016.148
|View full text |Cite
|
Sign up to set email alerts
|

RECOLLECTION OF WHAT-WHERE-WHICH MEMORY IN DEGUS (<i>OCTODON DEGUS</i>)

Abstract: To examine if a feature of episodic-like memory reported in rats is shared with other species, we investigated whether degus would form an integrated memory of object (what), place (where), and context (which). We used two E-shaped mazes with different contexts regarding the wall and the floor. Degus were entered into the middle arm and first explored the maze with two trial-unique objects placed at each end of the backbone of the E, with their location reversed between contexts. After being habituated to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…In an alternative, non-foraging task of the WWW memory paradigm, degus were capable of recollecting the integrated memory of content ("what") and location ("where"), along with the environmental context ("on which occasion") (Betsuyaku et al, 2016). This finding, taken together with other positive reports in rodents (i.e.…”
Section: Retrieval Of Incidentally Encoded Memory In Non-primate Speciessupporting
confidence: 67%
“…In an alternative, non-foraging task of the WWW memory paradigm, degus were capable of recollecting the integrated memory of content ("what") and location ("where"), along with the environmental context ("on which occasion") (Betsuyaku et al, 2016). This finding, taken together with other positive reports in rodents (i.e.…”
Section: Retrieval Of Incidentally Encoded Memory In Non-primate Speciessupporting
confidence: 67%
“…In this study, we used exploratory behavior as a sign of information-seeking responses, as it is one of the standard behavioral indicators in research on rodents (e.g., Winters et al, 2008 ; Fonio et al, 2009 ; Binder et al, 2012 ; Betsuyaku et al, 2016 ; Thompson et al, 2018 ); furthermore, it requires little in the way of training. Numerous studies have shown that exploratory duration and frequency may increase in unpredictable or uncertain situations.…”
Section: Discussionmentioning
confidence: 99%